A recipe for antimicrobial stewardship success: Using intervention mapping to develop a program to reduce antibiotic overuse in long-term care. (5th November 2018) - Chambers, Andrea; MacFarlane, Sam; Zvonar, Rosemary; Evans, Gerald; Moore, Julia E.; Langford, Bradley J.; Augustin, Anne; Cooper, Sue; Quirk, Jacquelyn; McCreight, Liz; Garber, Gary
Abstract: Objective: To better understand barriers and facilitators that contribute to antibiotic overuse in long-term care and to use this information to inform an evidence and theory-informed program. Methods: Information on barriers and facilitators associated with the assessment and management of urinary tract infections were identified from a mixed-methods survey and from focus groups with stakeholders working in long-term care. Each barrier or facilitator was mapped to corresponding determinants of behavior change, as described by the theoretical domains framework (TDF). The Rx for Change database was used to identify strategies to address the key determinants of behavior change. Results: In total, 19 distinct barriers and facilitators were mapped to 8 domains from the TDF: knowledge, skills, environmental context and resources, professional role or identity, beliefs about consequences, social influences, emotions, and reinforcements. The assessment of barriers and facilitators informed the need for a multifaceted approach with the inclusion of strategies (1) to establish buy-in for the changes; (2) to align organizational policies and procedures; (3) to provide education and ongoing coaching support to staff; (4) to provide information and education to residents and families; (5) to establish process surveillance with feedback to staff; and (6) to deliver reminders. Conclusions: The use of a stepped approach was valuable to ensure that locally relevant barriers and facilitators to practice change were addressed in the development of a regional program to help long-term care facilities minimize antibiotic prescribing for asymptomatic bacteriuria. This stepped approach provides considerable opportunity to advance the design and impact of antimicrobial stewardship programs.